Experimental Investigations Towards Hole Accuracy In Micro-Drilling Of Carbon Fibre Reinforced Polymer Material - Md Nasir, Nur Syuhada; Ab Wahab, Norfariza; Sofian, Badri; Raja Abdullah, Raja Izamshah; Sasahara, Hiroyuki (Jan Evangelista Purkyne University, 2021)
Nowadays, Carbon Fibre Reinforced Polymer (CFRP) materials are extensively used as substitutes for metal parts in aircraft and automotive components since they are lighter in weight. However, micro drilling CFRP materials during the assembly process poses various challenges such as low hole accuracy and delamination. Hence, an experiment has been executed to investigate the influence of micro drilling parameters towards hole accuracy. The spindle speed and feed rate are the machining parameters that have been considered in this experiment. Three different optimum parameters have been obtained from previous experiments, involving the spindle speed combinations of 8,000, 10,762 and 11,017 min-1 with a feed rate of 0.01 mm/rev. A drill bit with a diameter of 0.9 mm is used to drill approximately 300 holes. It has been revealed that the combination of the spindle speed of 11,017 min-1 and feed rate of 0.01 mm/rev produce high hole accuracy at the 2nd hole compared to the 300th hole due to the presence of uncut fibres at the 300th hole which have reduced the hole area. Hence, outcome of this research could provide the benefit to the industries in term of manufacturing time and materials expenditure